2017
DOI: 10.1093/annonc/mdx069
|View full text |Cite
|
Sign up to set email alerts
|

Heart dose exposure as prognostic marker after radiotherapy for resectable stage IIIA/B non-small-cell lung cancer: secondary analysis of a randomized trial

Abstract: Z5 - 22461/2 - 2002-017 (German Federal Office for Radiation Protection).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…It is unclear which regions of the heart are most susceptible for radiation injury. The contribution of heart doses to mortality has not been consistently demonstrated [129][130][131], but it is preferred that heart doses be limited as much as possible.…”
Section: Fractionation For Stereotactic Body Radiotherapy (Sbrt)mentioning
confidence: 99%
“…It is unclear which regions of the heart are most susceptible for radiation injury. The contribution of heart doses to mortality has not been consistently demonstrated [129][130][131], but it is preferred that heart doses be limited as much as possible.…”
Section: Fractionation For Stereotactic Body Radiotherapy (Sbrt)mentioning
confidence: 99%
“…Prior studies in this setting focused primarily on the association between cardiac dosimetry and OS, reaching conflicting conclusions. [10][11][12][13] Furthermore, the data appear limited about the significance of specific types of cardiotoxicities and the relationship with doses to cardiac subvolumes. 14 We thus assessed these relationships within a modern cohort of inoperable NSCLC patients treated with curative standard-dose RT (median prescribed dose, 61.2 Gy) and concurrent chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…5 A large number of studies have shown that RIHD can occur in patients with breast cancer, childhood lymphoma, and other cancers decades after radiotherapy. [6][7][8] Until now, there was no standard diagnostic method for RIHD. Myocardial markers (including brain natriuretic peptide (BNP), pro-BNP, and cTnI), echocardiography, and cardiac magnetic resonance are common methods for diagnosing RIHD.…”
Section: Introductionmentioning
confidence: 99%